MICU1 and MICU2 play nonredundant roles in the regulation of the mitochondrial calcium uniporter - Kamer, Kimberli J (Blackwell Publishing Ltd, 2014)
The mitochondrial uniporter is a selective Ca(2+) channel regulated by MICU1, an EF hand-containing protein in the organelle's intermembrane space. MICU1 physically associates with and is co-expressed with a paralog, MICU2. To clarify the function of MICU1 and its relationship to MICU2, we used gene knockout (KO) technology. We report that HEK-293T cells lacking MICU1 or MICU2 lose a normal threshold for Ca(2+) intake, extending the known gating function of MICU1 to MICU2. Expression of MICU1 or MICU2 mutants lacking functional Ca(2+)-binding sites leads to a striking loss of Ca(2+) uptake, suggesting that MICU1/2 disinhibit the channel in response to a threshold rise in [Ca(2+)]. MICU2's activity and physical association with the pore require the presence of MICU1, though the converse is not true. We conclude that MICU1 and MICU2 are nonredundant and together set the [Ca(2+)] threshold for uniporter activity.